Análise genética e citogenética do complexo Physalaemus cuvieri– Physalaemus ephippifer (Anura, Leptodactylidae) : Genetic and cytogenetic analyses of the Physalaemus cuvieri-Physalaemus ephippifer species complex (Anura, Leptodactylidae) - Tenório, Renata de Oliveira, 1989- (2020)
Orientador: Luciana Bolsoni Lourenço Morandini